The Long Shadow of the Ancient Greek and Latin Languages on the English Language from around 1600 Onwards - Muzaffar, Dr. Faisal (ACADEMIA International Journal for Social Sciences, 2026)
A few words with now and then differing alphabets! But the English language exhibits remarkable heterogeneity, i.e. the consequence of centuries of uninterrupted contact with other languages, because of its enormous lexical variety. Among them, Latin, French and Greek have been particularly extensive and consequential structurally. Despite the fact that their impact on English dates back to the long before the 17th cent, this article asserts that it, in fact, grew rather than declined after that point. A decisive promotion of English as a territorial language to a transcontinental language of science, government, and culture occurred in the seventeenth century. With the interdisciplinary approach that includes historical linguistics, sociolinguistics, lexical semantics and discourse analysis, the book looks into the reasons of Latin/French/Greek dependency in the 17th century up through the present and how English has been learning vocabulary. Study borrowing tendencies, coinage of neologisms, stratification of the register and institutional language use: Classical influences are revealed as having permeated the English language in expressive accuracy, flexibility of style and world coverage. The inquiry then finds that the extension of English as a world language has been necessarily coupled with its further dependence on classical and Romance linguistic resources.